Pelatihan Komunikasi Asertif untuk Meningkatkan Pengetahuan Pencegahan NAPZA Pada Siswa Sekolah Sekolah Dasar di Desa Medalsari Kabupaten Karawang - Ahmad Rifqy Ash-Shiddiqy; Happy Karlina Mardjo; Sigit Widiatmoko; Lalan Erlani (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
The high rate of drug abuse among elementary school students in Karawang Regency poses a significant challenge for teachers in implementing both preventive and curative measures. One proposed solution is to conduct an assertive communication training program aimed at enhancing students' knowledge about drug prevention. This community service initiative was carried out at SDN Medalsari 3, located in Medalsari Village, Karawang Regency, to evaluate the effectiveness of the training. The findings demonstrated that the assertive communication training program effectively improved elementary school students' knowledge of drug prevention. Based on these results, it is recommended that the Medalsari Village government and school leaders continue to support and organize assertive communication training programs as a preventive measure. Such efforts should be prioritized early in the developmental stages of children, particularly for students at SDN Medalsari 3, to reduce the risk of drug abuse.